Introduction of a new science program in schools of Uzbekistan - Abdumuminova Ozoda Anvarovna; Khalilova Valentina Vladimirovna (Zien Journals, 2024)
This article discusses the new subject Science in schools of Uzbekistan and its hours by grade
Keywords: Education; science; natural science; class